Subversion of Mucosal Barrier Polarity by Pseudomonas Aeruginosa - Engel, Joanne; Eran, Yonatan (Frontiers in Microbiology, 2011)
The lumenal surfaces of human body are lined by a monolayer of epithelia that together with mucus secreting cells and specialized immune cells form the mucosal barrier. This barrier is one of the most fundamental components of the innate immune system, protecting organisms from the vast environmental microbiota. The mucosal epithelium is comprised of polarized epithelial cells with distinct apical and basolateral surfaces that are defined by unique set of protein and lipid composition and are separated by tight junctions. The apical surface serves as a barrier to the outside world and is specialized for the exchange of materials with the lumen. The basolateral surface is adapted for interaction with other cells and for exchange with the bloodstream. A wide network of proteins and lipids regulates the formation and maintenance of the epithelium polarity. Many human pathogens have evolved virulence mechanisms that target this network and interfere with epithelial polarity to enhance binding to the apical surface, enter into cells, and/or cross the mucosal barrier. This review highlights recent advances in our understanding of how Pseudomonas aeruginosa, an important opportunistic human pathogen that preferentially infects damaged epithelial tissues, exploits the epithelial cell polarization machinery to enhance infection.